Development of wrestling mat materials to achieve better mechanical properties and improve the safety of the athletes - Tomin, M.; Kmetty, A. (British Journal of Sports Medicine, 2021)
Background The quality of wrestling mats plays a major factor in minimizing the rate and severity of injuries. However, the last known studies on the topic were conducted more than 40 years ago, and scientific background for the current mat requirements is not available.